Hybrid montmorillonite/cellulose nanowhiskers reinforced polylactic acid nanocomposites: a comparative study based on formulation design - Arjmandi, R. (Elsevier Inc., 2017)
The effects of formulation design on the tensile, morphological, and biodegradability properties of hybrid cellulose nanowhiskers/montmorillonite (CNW/MMT) reinforced polylactic acid (PLA) nanocomposites were investigated in this chapter. The CNWs were obtained from microcrystalline cellulose (MCC) using chemical swelling with N,. N-dimethylacetamide containing 0.5% lithium chloride. Based on the tensile properties of PLA/MMT nanocomposites, 5 phr (parts per hundred parts of resin) MMT was selected as optimum content (P/MT5/CW0). The PLA/MMT/CNW hybrid nanocomposites were prepared using two different sets of formulations by solution casting method. The hybrid nanocomposites were produced by incorporation of different content of CNW (1, 3, 5, 7, and 9 phr) into P/MT5/CW0 nanocomposite and partial replacement of MMT with CNW at total filler content of 5 phr. The highest tensile strength for the PLA/MMT/CNW hybrid nanocomposites was obtained at 1 phr CNW for both sets of formulations. Interestingly, the ductility of the hybrid nanocomposites increased remarkably from approximately 10 to 90 and 79% by incorporation of 1 phr CNW into P/MT5/CW0 nanocomposite and partial replacement of 1 phr MMT with CNW, respectively. Furthermore, the biodegradability of PLA/MMT/CNW hybrid nanocomposites improved compared to neat PLA and optimum formulation of PLA/MMT nanocomposites.